2010
DOI: 10.1002/jcp.22285
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of DNA‐binding and growth‐suppressive activity of mutant forms of p53 via a PCAF‐mediated acetylation pathway

Abstract: Tumor-derived mutant forms of p53 compromise its DNA binding, transcriptional, and growth regulatory activity in a manner that is dependent upon the cell-type and the type of mutation. Given the high frequency of p53 mutations in human tumors, reactivation of the p53 pathway has been widely proposed as beneficial for cancer therapy. In support of this possibility p53 mutants possess a certain degree of conformational flexibility that allows for re-induction of function by a number of structurally different art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…4). This result, while unexpected, is not unparalleled, as a number of studies have shown that mutant p53 protein is capable of binding to its target gene sequences and regulating their expression (Pan and Haines, 2000;O'Farrell et al, 2004;Weisz et al, 2007;Chandrachud and Gal, 2009;Perez et al, 2010;Rasti et al, 2012). Since the mutant p53 did not associate with the 14-3-3s promoter in the absence of plakoglobin (SCC9 cells), this suggests a role for plakoglobin in associating p53 with its target gene promoter(s).…”
Section: Discussionmentioning
confidence: 84%
“…4). This result, while unexpected, is not unparalleled, as a number of studies have shown that mutant p53 protein is capable of binding to its target gene sequences and regulating their expression (Pan and Haines, 2000;O'Farrell et al, 2004;Weisz et al, 2007;Chandrachud and Gal, 2009;Perez et al, 2010;Rasti et al, 2012). Since the mutant p53 did not associate with the 14-3-3s promoter in the absence of plakoglobin (SCC9 cells), this suggests a role for plakoglobin in associating p53 with its target gene promoter(s).…”
Section: Discussionmentioning
confidence: 84%
“…The expression of p53R175H, p53G281D or p53G245A in the p53 null H1299 cell lines increased the levels of endogenous CIC protein compared to naive H1299 cells (Figure 2AB), while wild-type p53 did not (Figure 2A, lane 2). In isogenic murine mammary breast cancer cell lines either lacking p53, harboring a wild-type gene or carrying the p53G242A codon (equivalent to the human G245A mutation) [24-26], high CIC levels were seen in cells expressing mutant but not wild-type p53 (Figure 2C). Additionally, down-regulation of p53R280K or p53R273H in MDA-231 or MDA-468 cells, respectively, with the previously described specific p53shRNA [9,24] reduced the levels of endogenous CIC (Figure 2DE).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, acetylation of the mutant p53 has been found to restore the DNA binding ability and the growth suppression function. 44 Since p53 methylation at K372 promotes its subsequent acetylation, 40,45 it is possible that KDM3A knockdown might reactivate mutant p53 by increasing p53 acetylation. Growing evidence suggests that breast CSCs are chemoresistant and highly invasive which might be associated with disease relapse.…”
Section: Discussionmentioning
confidence: 99%